Growth Response of Edamame Soybean (Glycine max (L.) Merr.) with Application of Urea and Rhizobium Biofertilizer on Peat Soil Media - Wita Purnama Sari; Dewi Erika Adriani; Chatimatun Nisa (TROPICAL WETLAND JOURNAL, 2021)
Edamame is a type of soybean that is consumed in an immature period. High demand for market exports especially to Japan, must be balanced by maximizing production with the use of marginal lands. One of marginal lands is peatland which might be used as growth media for edamame with Urea and Rhizobium biofertilizer application to support its growth. The recent study aimed at analyzing the combination of Urea and Rhizobium biofertilizer on the growth of edamame on peat soil media. The experiment was laid out in. Completely Randomized Design (CDR) with two factors. First factor was Urea dosage: p1 = 50 kg ha-1, p2 = 150 kg ha-1, p3 = 100 kg ha-1, p4 = 200 kg ha-1. The second factor was Rhizobium biofertilizer treatment: r0 = without Rhizobium biofertilizer and r1 = Rhizobium biofertilizer 8g kg-1 edamame seeds. All combination was repeated 3 times with 3 polybags of them, so that there were 72 plants in total. The results showed that there was a response between application of Urea and Rhizobium biofertilizer have a significant effect on the observed parameters, that is plant height (cm), number of trifoliate leaves (straind), shoot dry weight (g) and root dry weight (g). The result showed that the application of Urea 50 kg ha-1 with Rhizobium biofertilizer increased plant growth of edamame on peat soil. Keywords: Biofertilizer, Edamame soybean, Fresh vegetable, Wetland